Resilient Traditions: Exploring the Cultural Meaning of Javanese Wayang Kulit in Heritage Preservation - Arifin, Asman; Karen , Lidya (Insan Akademika Publications, 2024)
This research delves into the profound significance of Javanese shadow puppetry, or Wayang Kulit, in preserving and promoting Javanese cultural heritage. Wayang Kulit is not merely a traditional art form; it is a dynamic and resilient force that continues to breathe life into Javanese culture. This study explores the multifaceted dimensions through which Wayang Kulit contributes to the maintenance of Javanese cultural heritage. The research underscores the profound cultural importance of Wayang Kulit, serving as a living archive of Javanese traditions, myths, and history. It acts as a vehicle for the transmission of cultural values and ethical lessons, serving as a moral compass for the Javanese community. The economic significance of Wayang Kulit is undeniable, as it supports a network of local artisans, puppet makers, musicians, and businesses, benefiting local economies and sustaining livelihoods. Additionally, it attracts cultural tourists, providing a boon to local industries. Wayang Kulit fosters community cohesion, intergenerational bonds, and a profound sense of cultural identity among the Javanese people. It is a unifying force that strengthens familial ties and brings communities together. Wayang Kulit is more than an art form; it is a guardian of cultural heritage, an educator, and an economic force. Its resilience and adaptability serve as a model for the world, reaffirming the timeless value of cultural traditions in an ever-changing global landscape.